Chemotherapy and Quality of Life in Breast Cancer Patients: A Case-Series Study in Palembang, Indonesia - Eka Satyani Belina; Mulawan Umar; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Breast cancer is a prevalent malignancy affecting women worldwide, and its treatment, particularly chemotherapy, can significantly impact patients' quality of life (QoL). This study aimed to assess the QoL of breast cancer patients undergoing chemotherapy in Palembang, Indonesia, and to identify factors associated with their QoL. Methods: A cross-sectional study was conducted at the Oncology Unit of Dr. Mohammad Hoesin General Hospital in Palembang, Indonesia, from December 2024 to January 2025. A total of 150 breast cancer patients who met the inclusion criteria were enrolled in the study. Data were collected through medical records and the Functional Assessment of Cancer Therapy - Breast (FACT-B) questionnaire. The FACT-B assesses QoL in five domains: physical, social/family, emotional, functional, and breast cancer-specific concerns. Descriptive statistics, Spearman's correlation, and logistic regression were used to analyze the data. Results: The majority of the patients were aged 40-60 years (70%), had low educational levels (41.3%), were married (83.3%), had locally advanced disease (44%), and had completed chemotherapy (41.3%). The mean FACT-B total score was 76.8. A significant negative correlation was found between the intensity of chemotherapy and QoL (r = -0.306, p = 0.000). Logistic regression analysis revealed that patients who had completed chemotherapy had a significantly lower QoL than those who had not undergone chemotherapy (OR = 0.30, 95% CI = 0.15-0.60, p = 0.001). Conclusion: Chemotherapy significantly impacts the QoL of breast cancer patients in Palembang, Indonesia. Patients who have completed chemotherapy have a lower QoL than those who have not undergone chemotherapy. These findings highlight the importance of providing comprehensive supportive care to breast cancer patients undergoing chemotherapy to improve their QoL.